Effect of antihelminths with contrasting efficacy against gastrointestinal nematodes on the live-weight gain of young Nellore cattle - das Neves, José Henrique [UNESP]; Carvalho, Nadino; dos Santos, Nayara Capaldi [UNESP]; Júnior, João Ratti [UNESP]; Martins, Cyntia L. [UNESP]; Amarante, Alessandro F.T. [UNESP] (Elsevier, 2021)
We estimated the losses caused by gastrointestinal nematode (GIN) infections in young Nellore cattle born in three consecutive calving seasons (Cycles I, II and III). Three groups of animals: Group 1 - free from GIN using 2.5 mg/kg of albendazole sulfoxide; Group II - free from Oesophagosomum radiatum using 0.2 mg/kg of ivermectin but infected with ivermectin-resistant Haemonchus placei and Cooperia spp.; and Group III - non-treated experimental control animals, infected with all GIN, were observed over a period of 12 months. Male and female calves were evaluated starting before weaning when the animals were an average of approximately four months of age. In Cycle I, only females were evaluated. All the animals continued to graze on pastures of Urochloa spp. (= Brachiaria). All the groups showed median faecal egg counts of fewer than 250 eggs per gram (EPG), and no clinical signs of parasitic gastroenteritis were observed. The blood variables were within the normal ranges, and no calf presented anaemia. In most of the samplings, the median EPGs were significantly lower (P < 0.05) in the group treated with albendazole. Throughout the experiment, the most prevalent parasite observed in the control group was Cooperia spp., followed in decreasing order by Haemonchus spp., O. radiatum and Trichostrongylus spp. All the groups of calves exhibited weight gain throughout the trials with control group displaying the lowest body weight gain. Body weight variables between the albendazole- and ivermectin-treated groups were not significantly different (P > 0.05). After weaning, females animals in albendazole and ivermectin treated groups exhibited higher body weights, 20.4% and 22.7%, respectively, than those of the control group. Likewise, males treated with albendazole and ivermectin exhibited 27.6% and 25.8%, respectively, more body weight gain than animals under control group. Because the main difference between the ivermectin and the control groups was the O. radiatum parasitism, most of the losses in the control group were possibly due to this nematode species. Nevertheless, the other nematodes species that occurred in relatively high intensities in control group could also have an additive effect in such losses.
Keywords: Albendazole; Anthelmintic resistance; Bovine; Cooperia; Haemonchus; Ivermectin; Oesophagostomum